Gender Equality and Social Inclusion (GESI) in Village Development - Samsiah Nelly (IHSA Institute, 2021)
In compliance with the implementation of village government regulations concerning community empowerment and village development, this paper aims to provide an overview of the evolving paradigm of sustainable development and village opportunities in gender equity and social inclusion (GESI). This paper is a study of the literature based on data and information gathered from books, scientific papers, journals, and gender-related laws and policies. Gender mainstreaming policies were provided, as well as involvement of women in development. This policy would ensure that women will thrive and perform their social roles effectively. The study revealed that in some areas, initiatives to create inclusive village development have emerged, motivated by a desire to enhance people's rights fulfillment. Village planning must be approached from a GESI perspective, with no distinction made between men and women's positions, and marginalized groups' rights must be preserved.